The impact of smart transformer on different radial distribution systems - Ibrahem Mohamed A. Mahmoud; Tarek Saad Abdelsalam; Rania Swief (Archives of Electrical Engineering, 2021)
The work is intended to extend the application of a smart transformer on a radial distribution system. In this paper, an updated algorithm on the backward/forward power flow is introduced. The so-called direct approach of power flow is employed and analyzed. In addition, the paper focused on integrating a smart transformer to the network and solving the updating network also using the direct approach load flow. The solution of the smart transformer using the direct approach power flow method is quite straightforward. This model is applied to radial distribution systems which are the IEEE 33- and IEEE 69-bus systems as a case study. Also, the paper optimizes the best allocation of the smart transformer to reduce the power losses of the grid.